A qualitative study of leadership characteristics among women who catalyze positive community change - Folta Sara C; Seguin Rebecca A; Ackerman Jennifer; Nelson Miriam E (BMC, 2012)
Abstract Background Leadership is critical to making changes at multiple levels of the social ecological model, including the environmental and policy levels, and will therefore likely contribute to solutions to the obesity epidemic and other public health issues. The literature describing the relative leadership styles and strengths of women versus men is mixed and virtually all research comes from sectors outside of public health. The purpose of this qualitative study is to identify specific leadership skills and characteristics in women who have successfully created change predominantly within the food and physical activity environments in their communities and beyond. The second purpose of this study is to understand best practices for training and nurturing women leaders, to maximize their effectiveness in creating social change. Methods Key informant interviews were conducted with 16 women leaders in the public health sector from November 2008 through February 2010. The sample represented a broad spectrum of leaders from across the United States, identified through web searches and through networks of academic and professional colleagues. Most were working on improving the food and physical activity environments within their communities. Questions were designed to determine leaders' career path, motivation, characteristics, definition of success, and challenges. The initial coding framework was based on the questioning structure. Using a grounded theory approach, additional themes were added to the framework as they emerged. The NVivo program was used to help code the data. Results Respondents possessed a vision, a strong drive to carry it out, and an ability to mobilize others around the vision. Their definitions of success most often included changing the lives of others in a sustainable way. Persistence and communications skills were important to their success. The mentoring they received was critical. Challenges included fundraising and drifting from their original mission. Conclusions These findings may be used to help develop or inform a model of women's leadership in public health and to improve the training and nurturance of leaders who promote health in their communities and beyond.